1992
DOI: 10.1007/bf01959084
|View full text |Cite
|
Sign up to set email alerts
|

Statural growth in Williams-Beuren syndrome

Abstract: The spontaneous growth of 165 patients (75 girls and 90 boys) with Williams-Beuren syndrome was analysed in a mixed longitudinal and cross-sectional manner. Mean (+/- 1 SD) length at birth was 48.2 +/- 2.6 cm in girls (n = 52) and 49.0 +/- 3.0 cm in boys (n = 65). Intrauterine growth retardation (length below -2 SD of the normal population) was present in 35% of the girls and 22% of the boys. Poor growth was noted during the first 2 years of life. Until age 9 years in girls and 11 years in boys, mean growth fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 15 publications
2
51
0
2
Order By: Relevance
“…Weight gain was observed in most cases after the age of 10, in contrast with the OFC and the height, which followed the anticipated growth parameters (23). It has been reported that the mean final height of girls and boys with WS is 153.9 Ϯ 6.9 cm and 168.2 Ϯ 6.9 cm, respectively (25).…”
Section: Discussionmentioning
confidence: 80%
“…Weight gain was observed in most cases after the age of 10, in contrast with the OFC and the height, which followed the anticipated growth parameters (23). It has been reported that the mean final height of girls and boys with WS is 153.9 Ϯ 6.9 cm and 168.2 Ϯ 6.9 cm, respectively (25).…”
Section: Discussionmentioning
confidence: 80%
“…Age-related reference values for height, weight, and BMI were obtained from specific WBS charts [16][17][18] for WBS patients and from a wide sample of Italian children for healthy controls. 19 Height and BMI were normalised for chronological age by converting to SDS.…”
Section: Study and Laboratory Methodsmentioning
confidence: 99%
“…Weight was determined to the nearest 0.1 kg on a standard physician's beam scale, with the subject dressed only in light underwear and no shoes. Height, weight and pubertal stages were assessed according to international growth standards for WBS [16,17,18]. BMI was calculated and used as an indication of body fat mass.…”
Section: Methodsmentioning
confidence: 99%